2001
DOI: 10.1007/s11661-001-0164-0
|View full text |Cite
|
Sign up to set email alerts
|

Mean strain effects on the fatigue properties of superelastic NiTi

Abstract: lowered from 110 J in the peak-aged condition (5 hours) to but not in high-cycle fatigue. This difference is also reflected 70 J in the overaged condition (10 hours). Since the fracture in the S-N curves, where lines with different slopes are occurred in a mostly transgranular manner, [8,9] the embrittleneeded to fit the high-cycle and low-cycle data. ment was not severe, as compared to the intergranular The martensitic transformation is the basis of the superembrittlement, which produced very low impact toug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 5 publications
2
21
0
Order By: Relevance
“…Testing under simulated in vivo conditions of processoptimized Nitinol is then required to gain insight into the fatigue behavior of biomedical devices. Tabanli et al (Ref 14,15) were the first to explore the effects of mean strain on the fatigue behavior of superelastic Nitinol hypotubing (A f = 5°C). Room temperature cycling was conducted at a constant strain amplitude of $0.22%.…”
Section: Mechanical Fatiguementioning
confidence: 99%
“…Testing under simulated in vivo conditions of processoptimized Nitinol is then required to gain insight into the fatigue behavior of biomedical devices. Tabanli et al (Ref 14,15) were the first to explore the effects of mean strain on the fatigue behavior of superelastic Nitinol hypotubing (A f = 5°C). Room temperature cycling was conducted at a constant strain amplitude of $0.22%.…”
Section: Mechanical Fatiguementioning
confidence: 99%
“…Thus, the increase of the external twist leads to an increase of the effective mean strain during BRF cycling; and it has been observed that a non-zero mean strain may well increase the fatigue life of NiTi under certain circumstances [25].…”
Section: Resultsmentioning
confidence: 99%
“…Fatigue strength was assessed using Goodman diagram recommended by FDA for the analysis of this kind [13][14][15]. This method realizes the concept of infinite fatigue life (IFL).…”
Section: Methodsmentioning
confidence: 99%